Performance styles of Bukhara hafiz in Uzbek musical art - Sadriddin Gulov (Miasto Przyszłości, 2023)
As one of the foundations of performing-musical art, it is the process that expresses its existence, the criterion that determines its condition, and the factor that determines the level of skill. Performance styles of Bukhara hafiz can be said to be the practice of Shashmaqom performance tradition. At the moment, the Bukhara traditional singing school is being adequately continued by knowledgeable masters